Perspectives of UK Pakistani women on their behaviour change to prevent type 2 diabetes: qualitative study using the theory domain framework. Issue 7 (8th July 2014) - Penn, Linda; Dombrowski, Stephan U; Sniehotta, Falko F; White, Martin
Abstract : Background: Type 2 diabetes (T2D) is a debilitating disease, highly prevalent in UK South Asians, and preventable by lifestyle intervention. The 'New life, New you' (NLNY) physical activity (PA) and dietary intervention for T2D prevention was culturally adapted to better engage minority ethnic populations and tested for feasibility. Objectives: To investigate Pakistani female participants' perspectives of their behaviour change and of salient intervention features. Setting: A community-based 8-week programme of group delivered PA sessions with behavioural counselling and dietary advice, culturally adapted for ethnic minority populations, in an area of socioeconomic deprivation. Participants to NLNY were recruited through screening events in community venues across the town. Participants: Interviews were conducted with 20 Pakistani female NLNY participants, aged 26–45 (mean 33.5) years, from different parts of town. Results: Within the a priori Theoretical Domains Framework (intentions and goals, reinforcement, knowledge, nature of the activity, social role and identity, social influences, capabilities and skills, regulation and decision, emotion and environment), we identified the importance of social factors relating to participants' own PA and dietary behaviour change. We also identified cross-cutting themes as collateral benefits of the intervention including participants' 'psychological health'; 'responsibility' (for others' health, especially family members included in the new PA and diet regimes) and 'inclusion' (an ethos of accommodating differences). Conclusions: Our findings suggest that culturally adapted interventions for Pakistani women at risk of T2D, delivered via group PA sessions with counselling and dietary advice, may encourage their PA and dietary behaviour change, and have collateral health and social benefits. The NLNY intervention appeared to be acceptable. We plan to evaluate recruitment, retention and likely effect of the intervention on participant behaviour prior to definitive evaluation.